Investigation of the formation of Cu4SnS4 using mechanical alloying and heat-treatment for thermoelectric conversion - Le, Dai; Nguyen, Tien Anh; Nguyen Thi, Kieu Oanh; Le, Bang; Bui, Long (Vietnam Journal of Science and Technology, 2025)
Thermoelectric (TE) material is capable of directly converting heat energy into electricity without emitting gas. Cu-based chalcogenide materials, in particularly Cu4SnS4 are potential candidates for TE application due to their low thermal conductivity ( ), relatively high Sebeeck coefficient (S) and suitable bandgap energy, and composition of earth abundant, low cost, and less toxic elements.  In this research, Cu4SnS4 was synthesized using mechanical alloying method from Cu, Sn and S powders for different milling duration from 0 hour, 8 hours, 16 hours, and 20 hours in high purity Ar atmosphere. The 16 h-milling powder was heat-treated for investigation the phase transformation and sintered using spark plasma sintering (SPS) for TE properties characterization. As the results, the particle sizes of milled powders were rapidly decreased after 8 h milling and slightly decreased with further increasing in milling duration up to 16 hours and 20 hours. Cu3SnS4 began to form after milling for 8 hours and completed formation at 16 hours. With prolonged milling duration to 20 hours, it was still not possible to detect any trace formation of Cu4SnS4.  After heat-treatment at 673 K, the Cu3SnS4 phase of 16 h-milling powder was completely converted to Cu4SnS4. The electrical conductivity ( , Seebeck coefficient and power factor (PF) of sintered Cu4SnS4 sample increased with the increase of measured temperature, reaching maximum values of 1207 S m-1, 250 μV K-1 and  75.5 μW K-2 m-1 at 723 K,  respectively